2012 50th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2012
DOI: 10.1109/allerton.2012.6483262
|View full text |Cite
|
Sign up to set email alerts
|

Toward sustainable networking: Storage area networks with network coding

Abstract: Abstract-This manuscript provides a model to characterize the energy savings of network coded storage (NCS) in storage area networks (SANs). We consider blocking probability of drives as our measure of performance. A mapping technique to analyze SANs as independent M/G/K/K queues is presented, and blocking probabilities for uncoded storage schemes and NCS are derived and compared. We show that coding operates differently than the amalgamation of file chunks and energy savings are shown to scale well with strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…We give a brief overview of the theoretical background presented in [1]. Consider a DC storing one or more copies of file f composed of T chunks f = {f 1 , .…”
Section: B Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…We give a brief overview of the theoretical background presented in [1]. Consider a DC storing one or more copies of file f composed of T chunks f = {f 1 , .…”
Section: B Theoretical Backgroundmentioning
confidence: 99%
“…Reference [1] showed that blocking probability is a function of the incoming user tra c. Using curl loader we measure P e b as a function of the number of users present in the system n. For each n, 50 trials were run and confidence intervals are calculated across all data points.…”
Section: B Blocking Probability Estimationmentioning
confidence: 99%
See 3 more Smart Citations